Respuesta :

Answer:

Solution point is (-1,-9)

Step-by-step explanation:

Put the value of y in the first equation into the second equation.

  • 2x + 5(3x - 5) = - 42            Remove the brackets on the left
  • 2x + 15x - 25 = - 42            Combine like terms on the left
  • 17x - 25 = - 42                     Add 25 to both sides
  • 17x - 25 + 25 = - 42 + 25    Do the addition
  • 17x = - 17                              Divide by 17
  • 17x/17 = -17/17                      Do the division
  • x = - 1    

=======

Solve for y

  • y = 3x - 6
  • x = -1
  • y = 3(-1) - 6
  • y = -3 - 6
  • y = - 9